The inquiry-based student book integrated with local resources: The impact on student science process skill - Rumalolas, Nuryanti; Rosely, Meilin S. Y.; Nunaki, Jan Hendriek; Damopolii, Insar; Kandowangko, Novri Y. (Journal of Research in Instructional, 2021)
Research by several researchers on Biology Education Research (BER) showed that science process skills (SPS) were still a little bit researched. The purposes of this research are to reveal the followings: (1) the potential of inquiry-based student books integrated with local resources to improve students' science process skills; and (2) the differences in boys and girls science process skills. An experiment using the factorial design (2 X 2) was done on 52 randomly-selected senior high school students. Data collection was used essay test, then analyzed using ANOVA. This research revealed that students' SPS experienced an improvement when they studied in an inquiry class supported by a student book integrated with local resources. There is no distinction in the science process skills of boys and girls students. Boys and girls have the same opportunity to develop their SPS.